Identifikasi Mutasi FecX Pada Gen BMP15 dan Pengaruhnya Terhadap Sifat Prolifik pada Kambing Lokal di Kabupaten Lombok Barat - Rahmat Agus Hidayat; Sulaiman Ngongu Depamede; Maskur Maskur (Faculty of Animal Husbandry, University of Mataram, 2015)
The aims of this study were to identify the mutations of FecX gene in the local goats and to analyze its polymorphism as well as its influence on the prolific nature of the local goats in West Lombok Regency, Indonesia. The study was conducted in the Immunobiology Laboratory of Mataram University, using DNA isolated from 100 blood samples of local female goats which have given birth of once to three times. The methods used were PCR-RFLP method and the PCR products were digested with HinfI restriction enzyme (G|ANTC) then analyzed visually based on DNA banding patterns on 2% agarose gels. The frequency of allele and genotype obtained, were then analyzed through a comparison with the secondary data of litter size obtained from the local goat keepers information. The results showed that the gene mutation of FecXG produced two alleles: